The Price Discovery Puzzle in Offshore Yuan Trading: Different Contributions for Different Contacts - DING, David K. (Institutional Knowledge at Singapore Management University, 2011)
The People’s Bank of China (PBC) lifted yuan trading restrictions in July of 2010 that led to offshore yuan spot trading in Hong Kong. Based on causality analyses, we find that price discovery is absent between the onshore and offshore spot markets. However, we document the presence of price discovery between onshore spot and offshore nondeliverable forward (NDF) rates. These seemingly inconsistent results present a puzzle wherein one offshore market appears to be more informationally integrated with the onshore market than another. We conclude that price discovery differences in the offshore markets stem from the offshore spot and forward contracts tracking different aspects of yuan rates (e.g., the offshore nondeliverable rate tracks onshore spot rates whereas the offshore spot rate tracks onshore interest rates). Moreover, the introduction of offshore spot trading in Hong Kong has led to an increase in cross‐market price discovery between onshore spot and offshore.